Hábitos e distúrbios do sono em escolares da rede municipal de ensino - Troncoso, Eliane Aparecida de Mello (2012)
Sleep disorders are not only a problem in Brazil, has become a worldwide public health condition, affecting people physically and emotionally, and even putting them in danger of life. Objectives: To identify, analyze and compare habits and sleep disturbances (SD) in a sample of students from municipal schools in a midsize city in the state of Sao Paulo. Method: A study descriptive, qualitative-quantitative, with data collection conducted between November and December 2009, 188 children between six and 11 years of municipal schools in the city of Sao Jose do Rio Preto, SP, from screenplay data demographic questions about sleep habits and the Sleep Disorders Scale for Children (EDSC), completed by the parents / caregivers. The same was conducted within the standards required by the Helsinki Declaration, Resolution 196/96 of the National Health Council (NHC) and approved by the ethics committee of the Faculty of Medicine of São José do Rio Preto (Number 316/269). Results: Overall, the results indicate that the prevalence of SD in the sample school Sao Jose do Rio Preto, hit rate higher than that reported in literature with greater frequency among those who studied in the morning, consistent with research area, and whose parents / caregivers are considered mulatto. Students belonging to families with more members showed a greater tendency to Sleep Disordered Breathing (SDB), those taking medication for SED, and those who complained of pain or discomfort, for all SD. Boys were more SD, poor sleep habits healthy and more probability to Sleep Hyperhidrosis (HS) and enuresis, compared to girls in the study, was found increased occurrence and association between HS and SDB. Students with behavioral problems, expulsion and insufficient grade school tended to some SD specific, indicating a relationship between the variables. With regard to the habits that influence the quality of sleep, significant amount of students took plenty of fluids, including milk, close to bedtime, some children from school B responded in the affirmative to play strong, and the school A to the games video game or computer. After lying down, was the high amount of which were sporadic use of television and slept without turning it off, irregularities in the time and place to sleep were also identified in both institutions, as well as the permanence of parents / caregivers in the room until the child fall asleep. Conclusions: The SH, SD poorly addressed by the scientific literature was identified with high frequency in the population studied, and the SDB. Participants who showed sleep habits that were unfavorable constitute a significant portion of the sample, that may be influencing both the quantity and quality of sleep, increasing the risks related to diseases, as well as interfering with the development of intellectual abilities and school behavior. More detailed studies on SH as well as surveys are suggested, and specialty specific assistance programs should be developed and deployed for this community.